The Economic Benefit of Sustainable Fisheries Management: A Case Study Approach - Chandrasekharan, G.; Radhakrishnan, R.; Rajesh, Deepa (International Journal of Accounting and Economics Studies, 2025)
Fish and fish products are essential for providing coastal residents with food security and are a significant source of protein. The state's fish production is directly impacted by changes in the production of Indian oil sardines and Indian mackerel, which make up the majority of Karnataka's overall fish production. A fishery's success is directly influenced by timely spawning and successful recruitment. It is well recognized that a number of environmental conditions, either alone or in combination, directly affect gonad maturation, spawning, and recruitment. The formation of optimal phytoplankton/zooplankton production, which is essential for the survival of the spawn and larvae, is caused by environmental factors, including temperature, salinity, DO, nutrients, etc., in the proper proportion. Because they affect fishing resources and have the potential to alter fish species' biological functioning, research on climate fluctuations and their effects on fisheries is crucial. Sometimes, the effects of climate change may be more widespread, leading to regime changes that alter the region's fishery distribution pattern in a number of ways. Some of the changes that could be anticipated include species succession, the emergence of new species and the elimination of others, shifts in the availability of food, compelled modifications to the biological patterns of the species, etc. This study has studied the changes, their causes, and how they might be minimized or advantageously implemented.